Assessing the Importance of Domestic Vaccine Manufacturing Centers: An Overview of Immunization Programs, Vaccine Manufacture, and Distribution - Rey-Jurado, Emma; Tapia, Felipe; Muñoz-Durango, Natalia; Lay, Margarita K.; Carreño, Leandro J.; Riedel, Claudia A.; Bueno, Susan M.; Genzel, Yvonne; Kalergis, Alexis M. (Frontiers in Immunology, 2018)
Vaccines have significantly reduced the detrimental effects of numerous human infectious diseases worldwide, helped to reduce drastically child mortality rates and even achieved eradication of major pathogens, such as smallpox. These achievements have been possible due to a dedicated effort for vaccine research and development, as well as an effective transfer of these vaccines to public health care systems globally. Either public or private institutions have committed to developing and manufacturing vaccines for local or international population supply. However, current vaccine manufacturers worldwide might not be able to guarantee sufficient vaccine supplies for all nations when epidemics or pandemics events could take place. Currently, different countries produce their own vaccine supplies under Good Manufacturing Practices, which include the United States, Canada, China, India, some nations in Europe and South America, such as Germany, the Netherlands, Italy France, Argentina and Brazil, respectively. Here, we discuss some of the vaccine programs and manufacturing capacities, comparing the current models of vaccine management between industrialized and developing countries. Because local vaccine production undoubtedly provides significant benefits for the respective population, the manufacture capacity of these prophylactic products should be included in every country as a matter of national safety.